Front Street after the big fire of April 1899, Dawson, May 15, 1899 - Curtis, Asahel, 1874-1941 (1899)
Photographs taken by Asahel Curtis during his trip to the Klondike in 1897-1899. Caption on image: Curtis 985 Handwritten on verso: Front St., Dawson, May 15, 1899. Building up after fire. PH Coll 519.985 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number